Countering Terrorism and Criminal Financing in Nigeria: Strategic Options - Falode , Adewunmi J.; Chukwuemeka, Nnamani E. (Razón Crítica, 2022)
This work analysis Nigeria’s effort to counter terrorism and criminal financing (TCF). It shows that criminal and terrorist organizations in fund their operations through an illegal financial infrastructure embedded in the Nigerian financial sector. To counter and deny access to funds that could be used to destabilize the state and compromise the integrity of financial institutions in the country to these malign non-state actors, Nigeria has deployed several strategies. By using qualitative research methodology, and a historical, descriptive, and narrative approach, it was discovered that Nigeria has used both government institutions, such as the Economic and Financial Crimes Commission (EFCC) and the Nigerian Financial Intelligence Unit (NFIU) and legal-cum financial instruments, such as the Terrorism (Prevention) (Amendment) Act (TPAA) and the Anti Money Laundering/Combating Financing of Terrorism (AML/CFT), to disrupt TCF in the country. In its conclusion, the work argues that Nigeria will have to be strategic in its response if it hopes to effectively counter TCF. This strategic response, this work show, will involve the extensive use of technical and financial expertise from international anti-money laundering bodies like the EGMONT Group and the Financial Action Task Force (FATF).